The Validity and Practicalily of Prezi Learning Media on the Role of Soil and Soil Organisms for Life Sustainability for Junior High School Students - Dina Hafizhah; Maya Istyadji; Sauqina; Fahmi (Postgraduate, University of Mataram, 2022)
Most science books do not provide easy-to-understand visual media. For example, by giving pictures that are small or unclear, so that students find it difficult to understand the available information. Therefore, a study was conducted on the validity and practicality of Prezi learning media on the role of soil and soil organisms for the survival of junior high school students. The purpose of this study was to test the validity and practicality of Prezi learning media. This study uses the Research and Development method with the ADDIE development model which is carried out only until the implementation stage with a small group scale. The research instrument used was the Prezi learning media validation sheet and student response questionnaires. Based on the results of the study, it was obtained that the validity test of the Prezi learning media was very valid by showing a score of 0.84 while the results of the student response questionnaire as a test of the practicality of the media were obtained practically by showing a score of 77%, so it can be concluded that the Prezi learning media can be continued to the next stage, namely the effectiveness stage